Ustalone Naprężenia w Walcu Ortotropowym oraz w Tarczy Ortotropowej - Nowacki, W. (Engineering Transactions, 1960)
In the first part of the paper conditions are established, in which the state of stress in an orthotropic cylinder in a steady-state sourceless temperature field is confined to one component only, the stress in the direction of the x-axis.In the second part of the paper a thin orthotropic plate is considered under a steady-state linear temperature field (in the direction of the x-axis). Conditions are established under which all the stress or displacement components vanish in a sourceless temperature field.